Measuring resilience in the aviation industry: a case study of a South African Company - Maphike, Tembisa (University of the Witwatersrand, Johannesburg, 2024)
For organizations operating in high-risk environments, resilience must be a top priority as a key component of their safety measures. In addition to applying Safety I principles, it is also crucial to implement Safety II principles to further improve resilience. This study examines the views of employees within the organization regarding four constructs of Resilience Engineering: the ability to respond, the ability to monitor, the ability to learn, and the ability to anticipate. The evaluation was conducted through an online survey instrument and the sample was drawn from the operational personnel population. Several tests were administered to characterize the sample, assess its reliability and validity, and conduct other analyses. The results indicate that while some elements of resilient performance are visible, the overall picture is that these elements need to be improved upon.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, In the Faculty of Commerce, Law and Management, School of Wits Business School, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Safety management systems; accidents; Resilience engineering; SDG-9: Industry, innovation and infrastructure; SDG-8: Decent work and economic growth